Sulle tracce del trauma - Cataldi, Domitilla (L’ospite ingrato, 2025)
In this paper, I will deal with abuse understood as trauma that, in a relationship between two people, violates the body. Clinical practice still reveals to us today the extent of the effects on an ego that is incapable of defending itself and of allowing the excitatory, incomprehensible and ruinous charge of an abusive adult to flow out of itself. In this sense, the theoretical clinical contribution of Ferenczi, still remains essential today in approaching the complexity of the pathological dynamics of the traumatic scenario. A scenario that is explored here within the psychoanalytic relationship, through the therapist’s listening and welcoming towards the narrative fabric of the patient’s body and mind manifestations, in order to trace the abuse and return it to the vital dynamics of communication and thus be able to translate it, restoring meaning to it.